2015
DOI: 10.1093/jme/tju013
|View full text |Cite
|
Sign up to set email alerts
|

L1014F-kdr Mutation in Indian Anopheles subpictus (Diptera: Culicidae) Arising From Two Alternative Transversions in the Voltage-Gated Sodium Channel and a Single PIRA-PCR for Their Detection

Abstract: Leucine-to-phenylalanine substitution at residue L1014 in the voltage-gated sodium channel, target site of action for dichlorodiphenyltrichloroethane (DDT) and pyrethroids, is the most common knockdown resistance (kdr) mutation reported in several insects conferring resistance against DDT and pyrethroids. Here, we report presence of two coexisting alternative transversions, A>T and A>C, on the third codon position of L1014 residue in malaria vector Anopheles subpictus Grassi (species A) from Jamshedpur (India)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Currently no evidence of cross resistance to DDT and pyrethroids has been observed, however the study has underlined the existence of DDT resistance in malaria vectors and possible decline in sensitivity to the synthetic pyrethroids, but does not suggests the mechanism which could be attributed to the problem of resistance. Studies have very well documented the role of target-site mutations in insecticide resistance, however these were not found solely responsible for resistance and some detoxifying genes acting in concert with these mutations in voltage gated sodium channels were reported to confer extreme levels of resistance [ 28 , 35 39 ]. A recent research demonstrated that glutathione S-transferase gene GSTe2 was the most over-expressed detoxification gene in DDT and permethrin resistant Anopheles funestus mosquitoes [ 40 ], whereas another study [ 41 ] claimed that mutation L1014F was more efficient in conferring resistance to DDT as compared to pyrethroids, which might be a reason that the mosquitoes in the present study displayed high level of resistance to DDT.…”
Section: Discussionmentioning
confidence: 99%
“…Currently no evidence of cross resistance to DDT and pyrethroids has been observed, however the study has underlined the existence of DDT resistance in malaria vectors and possible decline in sensitivity to the synthetic pyrethroids, but does not suggests the mechanism which could be attributed to the problem of resistance. Studies have very well documented the role of target-site mutations in insecticide resistance, however these were not found solely responsible for resistance and some detoxifying genes acting in concert with these mutations in voltage gated sodium channels were reported to confer extreme levels of resistance [ 28 , 35 39 ]. A recent research demonstrated that glutathione S-transferase gene GSTe2 was the most over-expressed detoxification gene in DDT and permethrin resistant Anopheles funestus mosquitoes [ 40 ], whereas another study [ 41 ] claimed that mutation L1014F was more efficient in conferring resistance to DDT as compared to pyrethroids, which might be a reason that the mosquitoes in the present study displayed high level of resistance to DDT.…”
Section: Discussionmentioning
confidence: 99%
“…subpictus that had 100% genetic similarity with Sri Lankan An. subpictus species A in the mitochondrial cytochrome oxidase I gene [50]. Our results show that an A → C transversion that leads to the L1014F amino acid substitution is found in all 15 An.…”
Section: Discussionmentioning
confidence: 68%
“…In An. subpictus, an L1014F mutation is reported to arise from an A → T transversion in the North Central Province of Sri Lanka [49] and India [50] and an A → C transversion only in India [50]. Only one of 25 etofenprox resistant An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations that cause resistance are most commonly found in domain II region (between IIS4-5 linker and IIS6) of the VGSC protein where five residues have been implicated for resistance to date: Met918 in the IIS4-IIS5 linker, Leu925, Thr929 and Leu932 in IIS5 and Leu1014 in IIS6 [ 12 , 13 ]. The L1014F/S in IIS6 which is referred to as kdr mutation, confers knockdown resistance phenotype in anophelines [ 14 , 15 ] and has been reported in Anopheles gambiae, [ 16 , 17 ], Anopheles arabiensis [ 18 ], Anopheles stephensi [ 19 , 20 ], Anopheles sinensis and many other anophelines [ 21 , 22 ]. Recently L1014F/S mutation was reported in An.…”
Section: Introductionmentioning
confidence: 99%